Mathematical modeling of Microcystis aeruginosa growth and [D-Leu1] microcystin-LR production in culture media at different temperatures - Crettaz Minaglia, Melina Celeste (2017)
The effect of temperature (26 °C, 28 °C, 30 °C and 35 °C) on the growth of native CAAT-3-2005 Microcystis aeruginosa and the production of Chlorophyll-a (Chl-a) and Microcystin-LR (MC-LR) were examined through laboratory studies. Kinetic parameters such as specific growth rate (μ), lag phase duration (LPD) and maximum population density (MPD) were determined by fitting the modified Gompertz equation to the M. aeruginosa strain cell count (cells mL⁻¹). A 4.8-fold increase in μ values and a 10.8-fold decrease in the LPD values were found for M. aeruginosa growth when the temperature changed from 15 °C to 35 °C. The activation energy of the specific growth rate (Eμ) and of the adaptation rate (E1/LPD) were significantly correlated (R² = 0.86). The cardinal temperatures estimated by the modified Ratkowsky model were minimum temperature = 8.58 ± 2.34 °C, maximum temperature = 45.04 ± 1.35 °C and optimum temperature = 33.39 ± 0.55 °C. Mathematical modeling of Microcystis aeruginosa growth and [D-Leu 1 ] microcystin-LR production in culture media at different temperatures.